2020
DOI: 10.21203/rs.3.rs-28185/v5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Incentives to Improve HIV Prevention Outcomes for Young Females in Eswatini: Sitakhela Likusasa Impact Evaluation Protocol and Baseline Results

Abstract: Background: Eswatini continues to have the highest prevalence of HIV in the world, and one of the highest HIV incidences among adult populations (aged 15-49). This analysis reports on both key elements of study design/protocol and baseline results from an impact evaluation of an intervention incentivizing (i) initiation, enrolment, attendance or completion of some form of education, and (ii) lower risk sexual behaviour. Methods: The impact evaluation employs a two by two factorial design in which participants … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…CTs with augmented HIV interventions in African AGYW have shown potential to lower HSV‐2, reduce HIV incidence to various degrees, reduce transactional sex and reduce HIV risk behaviours [ 24 , 47 , 48 , 49 , 50 , 51 ]. Within these programmes, CTs have been strongly associated with attendance and/or adherence with the study intervention [ 24 , 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CTs with augmented HIV interventions in African AGYW have shown potential to lower HSV‐2, reduce HIV incidence to various degrees, reduce transactional sex and reduce HIV risk behaviours [ 24 , 47 , 48 , 49 , 50 , 51 ]. Within these programmes, CTs have been strongly associated with attendance and/or adherence with the study intervention [ 24 , 50 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…These approaches aim to reduce individual, social and structural barriers to safe behaviours and enhanced access to services [ 15 ]. The effectiveness of CT alone on SRH/HIV outcomes in AGYW has been disappointing [ 16 , 17 ] “Cash plus” interventions have been recommended as they augment CTs with life skills, behavioural interventions (BIs) and health systems strengthening that could promote protective SRH behaviours, as well as access to quality services [ 15 , 16 , 18 , 19 , 20 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the current study showed that only a few respondents supported the view that one should utilize HTS if becomes ill. Various motivations has been shown to increase uptake of HTS; however, studies evaluating the relationship between the use of financial incentives and uptake of HTS are limited [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Second, cash transfers are a primary delivery mechanism of social protection [7,24]. Because of their multiple impacts on health and development domains, cash transfers have heightened attention in HIV prevention and treatment efforts [15,16,18,25]. Third, children, adolescents, girls and women, people with disabilities, and older people, are often the focus populations of social protection programmes [7,24].…”
Section: Introductionmentioning
confidence: 99%